2019
DOI: 10.1101/800714
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Freezing displayed by others is a learned cue of danger resulting from co-experiencing own-freezing and shock

Abstract: SUMMARYSocial cues of threat are widely reported [1–3], whether actively produced to trigger responses in others, such as the emission of alarm calls, or by-products of an encounter with a predator, like the defensive behaviors themselves, such as an escape flight [4–14]. Although the recognition of social alarm cues is often innate [15–17], in some instances it requires experience to trigger defensive responses [4,7]. One mechanism proposed for how learning from self-experience contributes to social behavior … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 50 publications
2
16
0
Order By: Relevance
“…Sample size (N) reflects the number of actors included in the behavioral analyses. switching, in line with prior studies showing that prior experience increases sensitivity to others' pain as measured by vicarious freezing [9,16,19,21,22]. The behavior of the victim, in terms of USVs, pain squeaks, and freezing, in contrast, was not robustly associated with switching, but victims that decreased their time spent close to the divider (due to shockinduced behavioral activity) were paired with actors with higher switching scores.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Sample size (N) reflects the number of actors included in the behavioral analyses. switching, in line with prior studies showing that prior experience increases sensitivity to others' pain as measured by vicarious freezing [9,16,19,21,22]. The behavior of the victim, in terms of USVs, pain squeaks, and freezing, in contrast, was not robustly associated with switching, but victims that decreased their time spent close to the divider (due to shockinduced behavioral activity) were paired with actors with higher switching scores.…”
Section: Discussionsupporting
confidence: 84%
“…Third, we show that pre-exposure to shocks potentiates switching. It has been shown that freezing while observing another animal receive shocks is potentiated by prior shock experience [9,19,21,47], but other arousing experiences, such as a forced swim test, do not have the same potentiating effect [22,48]. Moreover, although [32,35] for muscimol (red) and saline (green) animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 It was proposed that during such pre-exposure, observers learn to associate freezing with aversive sensory stimulation, which makes emotional contagion possible. 40 Our data show that social information can elicit robust and flexible behavioral responses without any prior training, possibly through engaging different mechanisms-that is, change of the observers' state.…”
Section: Behavioral Resultsmentioning
confidence: 79%
“…A number of studies have examined vicarious freezing behavior as an indicator of empathy in rodents ( Atsak et al, 2011 ; Carrillo et al, 2019 ; Cruz et al, 2020 ; Han et al, 2020 ; Jeon et al, 2010 ; Pereira et al, 2012 ). In these studies usually an observer witnesses a demonstrator experience some kind of threat, most often a foot shock.…”
Section: Introductionmentioning
confidence: 99%